Sintang Dalisay: Reminiscing from a Technical Perspective - Cortezano, Daniel Roan V (Archīum Ateneo, 2020)
Biographical. The article focuses on the influence of Salvador Bernal which goes beyond the design work. The relationship between a National Artist and an emerging artist is set for discussion.